Phenotypic and molecular characterization of Pantoea agglomerans causing citrus canker of calamansi (Citrus microcarpa) in Selangor - Fung, Vincent Roderic Jr (2017)
Citrus microcarpa (C. microcarpa), commonly known as limau kasturi or calamansi fruit has been used widely in food preparation and antibacterial activities due to their strong bioactive components. It belongs to the family Rutaceae, and found native to Philippines and widely growing throughout South East Asia region. However, the infestations of canker disease can be induced by the Pantoea species (Pantoea spp.) as a causal agent, instead of Xanthomonas axonopodis pathovar citri. The symptoms of this disease include blister-like surrounded by yellow halos on the infected fruits and leaves that will later turn to yellow, and easily fall. This study was conducted to reach these objectives; 1) isolation and identification of Pantoea spp. isolated from local calamansi varieties via phenotypic characteristics and 2) molecular identification and phylogenetic analysis of Pantoea spp. strains isolated in this study. The samples of C. microcarpa with the symptoms of canker disease were obtained from Ladang 10, Universiti Putra Malaysia and were isolated to obtain pure cultures. Then, the characteristics of the causal bacterium were described through phenotypic characterization. The pure cultures were yellowish in color, Gram-negative with rod-shaped, positive reaction for catalase test and potassium hydroxide (KOH) tests; and negative for oxidase test. The pathogenicity test on four selected strains were showed, leaves started to change in terms of color and leaf-spot also occurred; and volcano-like symptoms, non-uniform lesion occurred on the fruits and started to fall which act as the citrus canker symptoms after seven days of inoculation into healthy calamansi seedlings. Negative control, seedlings remained asymptomatic. Strain cultures were re-isolated and the morphological and biochemical characteristics showed up as mentioned above. For molecular identification, the total genomic DNA of all four strains were extracted as templates for 16S rDNA polymerase chain reaction (PCR) amplification by using primer 8F and 1492R, where they produced ~1400bp amplicon each. Sequencing analyses showed that all strains were 99% identical to Pantoea agglomerans, reference gene in GenBank database. Phylogenetic analyses of the 16S rDNA gene sequences clustered all strains into Pantoea agglomerans, reference strains with 100% posterior probability. To our knowledge, this is the first report of citrus canker disease caused by Pantoea agglomerans of calamansi in Malaysia.